2019
DOI: 10.1182/blood-2019-123027
|View full text |Cite
|
Sign up to set email alerts
|

Definition and Validation of the New Elderly Prognostic Index (EPI) for Elderly Patients with Diffuse Large B-Cell Lymphoma Integrating Geriatric and Clinical Assessment: Results of the Prospective "Elderly Project" on 1353 Patients By the Fondazione Italiana Linfomi

Abstract: Introduction: Management of elderly patients with Diffuse Large B-Cell Lymphoma (DLBCL) is challenging. A simplified Comprehensive Geriatric Assessment (sCGA) based on ADL (Activity of Daily Living), IADL (Instrumental ADL) and CIRS-G (Comorbidity Index Rating Scale for Geriatrics) scales has demonstrated to be better than clinical judgement to stratify patients' outcome but has never been included in initial assessment. To further assess the impact of sCGA on patients' outcome, we conducted a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…A categorical prognostic index using a revised version of sCGA groups, the IPI and Hb levels was developed identifying three risk groups each associated with a different three‐year OS: the Low‐Risk group (23% of patients) had a three‐year OS of 87%, the Intermediate‐Risk group (48% of patients) had a three‐year OS of 69%, and the High‐Risk group (29% of patients), who had a three‐year OS of 42%. The index was validated in patients treated with ACRs and on an independent external series of patients 24 . This ‘Elderly Prognostic Index’ (EPI) is the first validated, prospective index to integrate GA with clinical features and may contribute to improving management and clinical research in elderly patients with DLBCL.…”
Section: Geriatric Assessment Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…A categorical prognostic index using a revised version of sCGA groups, the IPI and Hb levels was developed identifying three risk groups each associated with a different three‐year OS: the Low‐Risk group (23% of patients) had a three‐year OS of 87%, the Intermediate‐Risk group (48% of patients) had a three‐year OS of 69%, and the High‐Risk group (29% of patients), who had a three‐year OS of 42%. The index was validated in patients treated with ACRs and on an independent external series of patients 24 . This ‘Elderly Prognostic Index’ (EPI) is the first validated, prospective index to integrate GA with clinical features and may contribute to improving management and clinical research in elderly patients with DLBCL.…”
Section: Geriatric Assessment Toolsmentioning
confidence: 99%
“…The index was validated in patients treated with ACRs and on an independent external series of patients. 24 This 'Elderly Prognostic Index' (EPI) is the first validated, prospective index to integrate GA with clinical features and may contribute to improving management and clinical research in elderly patients with DLBCL. Whether the EPI or other scoring systems can be used to precisely direct the use of specific immunochemotherapy dose intensity and predict for fitness for anthracycline-based treatment remains an open question.…”
Section: Geriatric Assessment Toolsmentioning
confidence: 99%
“…According to the IPI score, there are significant differences in PFS and OS between the IPI ≤ 3 and IPI > 3 groups, suggesting that the IPI score could predict the prognosis in elderly patients. Recently, a study from Italy reported that combining the comprehensive geriatric assessment (CGA) with the IPI score could identify three risk groups with notable differences in terms of OS ( Spina et al, 2019 ; Merli et al, 2021 ), which would help clinicians to evaluate the prognosis of patients with greater precisely.…”
Section: Discussionmentioning
confidence: 99%
“…The improved survival seen for patients with aggressive lymphomas who received active treatment calls for better tools to evaluate treatment eligibility in the oldest old, to avoid diagnostic delay and to identify regimens with high tolerability. Currently, there are no perfect methods to do this as both the well‐validated Complete Geriatric Assessment (CGA) and Q8‐questionnarie have the inherent risk of interpreting lymphoma‐associated symptoms as frailty, 3,7,28 although a prognostic score integrating the CGA, IPI and haemoglobin value has demonstrated prognostic significance 29 . Further, more liberal use of RT and supportive drugs, such as granulocyte‐colony stimulating factors, optimisation of general health and involvement of family caregivers could potentially increase the number of patients eligible for active treatment 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no perfect methods to do this as both the well-validated Complete Geriatric Assessment (CGA) and Q8-questionnarie have the inherent risk of interpreting lymphoma-associated symptoms as frailty, 3,7,28 although a prognostic score integrating the CGA, IPI and haemoglobin value has demonstrated prognostic significance. 29 Further, more liberal use of RT and supportive drugs, such as granulocyte-colony stimulating factors, optimisation of general health and involvement of family caregivers could potentially increase the number of patients eligible for active treatment. 3 Prior studies have reported improved survival rates with pre-planned dose reductions among patients aged ≥85 years.…”
Section: Discussionmentioning
confidence: 99%